Visual indicator for the detection of methylmercury in blood: A critical biomarker for dietary exposure assessment - Yan Guo; Bing-chan Ma; Wen-qi Zhang; Bo-xin Li; Jia-ming Ou; Fen Liu; Chang-ye Hui (Ecotoxicology and Environmental Safety)
Methylmercury (MeHg), a significant dietary exposure biomarker, poses a substantial threat to public health, primarily due to the consumption of aquatic foods. Current detection methods are complex and unsuitable for on-site testing, necessitating the development of a simple and sensitive biosensor for rapid screening. This study addresses this challenge by developing a highly sensitive whole-cell biosensor for detecting organic mercury in blood samples, offering both visual qualitative and colorimetric quantitative assessments. We engineered a biosensor based on the mer operon and deoxyviolacein (DV) pigment, optimizing its performance by adjusting the MerB expression level, screening host cells, and incorporating the biosurfactant rhamnolipid. The optimized biosensor achieved a detection limit of 0.195 nM and exhibited a linear response range of 0.195–1.563 nM for MeHg. This range is significantly below the Provisional Tolerable Weekly Intake (PTWI) of 1.6 μg/kg body weight per week established by the Joint FAO/WHO Expert Committee on Food Additives (JECFA), ensuring the reliable detection of MeHg at concentrations well within the safety threshold. Notably, the biosensor demonstrated broad-spectrum detection capabilities, including natural MeHg and synthetic organomercurials, which are crucial for assessing dietary exposure risks from various sources. This study advances the development of a novel biosensor for MeHg detection, highlighting its potential as a critical tool for assessing dietary exposure risks and contributing to understanding food safety and public health.